The Sound of Trumpet will Stir the World and Raise the Dead: Prayers Accompanied by Brass Instruments in the Folk Piety Tradition - Žarskienė, Rūta (Tautosakos darbai, 2018)
The article focuses on a phenomenon that has so far evaded scholarly attention and research. Apparently, in Samogitia, where brass instruments still play at traditional Catholic or even Lutheran funerals and death anniversaries, participate in the Easter morning processions and the Catholic Church feasts (Lith. atlaidai), yet another practice of folk piety involving brass instruments is thriving: i.e. prayers at the graveside in summer time, during Catholic Church feasts and All Souls’ Day (more frequently still, All Saints’ Day). During her fieldwork of 2013–2017 in various parts of Mažeikiai and Skuodas districts, the author of the article gathered material on this folk piety practice in religious feasts of Saint Mary Magdalene, Saint Roch, and Saint Anne etc. taking place in Grūstė, Ylakiai, Židikai, Vaičaičiai and elsewhere. These feasts take place in cemeteries, while the Mass, their main sacral highlight, is performed in the cemetery chapel or in a nearby church. People gather to the feasts in order to visit the graves of their diseased and meet with their relatives, inviting brass musicians to perform the ritual at the graveside. The ritual comprises several parts: intention, the sign of the cross in the beginning and at the end, prayers (the Lord’s Prayer, the Hail Mary, and “Eternal Rest”), a stanza from a popular traditional religious hymn, which is both sung and played, the prayer “Eternal Rest”, which is both sung and played antiphonally this time, and traditional Catholic greeting (“Honor be to Jesus Christ”). These parts make up a slightly varying “scenario”, which usually takes 3 to 3,5 minutes to perform. The structure of ensembles (from 2 to 4 musicians), their age (from 12 to 83 years old), the actual instruments (trumpets, tuba, tenor, baritone, saxophone, etc.), and style of performance also vary. The self-educated musicians of the elder generation usually play in the traditional way, i.e. loudly, slowly and inaccurately. The younger generation representatives, usually having acquired some professional music education, have adopted more esthetic style of performance, using reduced volume and “intermediate” fragments to fill in the pauses. In 2017, the tendency was noted of forgoing prayers and including several stanzas of a particularly popular modern hymn instead of one. This would indicate an attempt at changing the tradition in order to adapt to the popular culture, or even belonging to it. In search for roots of this custom of folk piety, the author of the article employs the historical sources from the 17th–18th centuries. According to her analysis, the main point of the ritual – the prayer “Eternal Rest” – was actively used not only in the rituals of the 19th–20th century, but also as early as the Baroque period, while its origins may reach back to the medieval teachings on purgatory. The last line of this prayer (“May they rest in peace. Amen”) was used as a quiver prayer. The arrow as symbol was highly favored in Baroque heraldic, poetry, panegyrics; it used to be compared not only to prayer, but also to the loud and powerful sound of the brass instruments. The brass instruments acted as a concurrent accompaniment of both religious and secular festivals of the time, playing an important role both in the Roman Catholic and in the Evangelical Lutheran traditions. While seeking to clarify the reasons for trumpets being played at cemeteries and the meaning of this ritual, it appeared that in the Catholic Samogitia there still survives a belief in the trumpet accompanied prayer to have the power of alleviating the suffering of souls in the purgatory. People inviting the brass musicians to play at the graveside even in the modern times believe that such prayer goes straight to heaven and easily reaches the God.
Keywords: -